2009
DOI: 10.1002/gea.20277
|View full text |Cite
|
Sign up to set email alerts
|

Infrared reflection spectrometry analysis as a non‐destructive method of characterizing minerals and stone materials in geoarchaeological and archaeometric applications

Abstract: The purpose of this paper is to show the benefits and applications of using mid and far infrared reflection spectrometry (IRS) in the analysis of archaeological materials. Infrared spectral databases do not yet exist for rocks and principal minerals. In support of IRS techniques, a catalogue and new spectral database have been created with over 500 infrared reflection spectra in mid and far ranges from more than 250 different archaeological minerals and stone materials. The reflection spectrum serves as a "fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Archaeologists have been slow to realize the potential application of reflectance spectroscopy, although a few studies make note of the technique (Luedtke, 1992;Church, 1994;Carr & Turner, 1996;Long, Silveria, & Julig, 2001;Hubbard, Waugh, & Ortiz, 2005;Hubbard, 2006). The results of previous research indicate that various spectroscopy techniques are well suited to archaeological and geological applications (Carr & Turner, 1996;McCutcheon, 1997;McCutcheon & Kuehner, 1997;Emerson & Hughes, 2000;Long, Silveira, & Julig, 2001;Wisseman et al, 2002;DeSouza et al, 2003;Lyons, Glascock, & Mehringer, 2003;Hubbard, Waugh, & Ortiz, 2005;Hubbard, 2006;Bowitz & Ehling, 2008;Hawkins et al, 2008;Ostrooumov, 2009;Parish, 2009;Wisseman et al, 2010).…”
Section: Vnir Spectroscopymentioning
confidence: 90%
“…Archaeologists have been slow to realize the potential application of reflectance spectroscopy, although a few studies make note of the technique (Luedtke, 1992;Church, 1994;Carr & Turner, 1996;Long, Silveria, & Julig, 2001;Hubbard, Waugh, & Ortiz, 2005;Hubbard, 2006). The results of previous research indicate that various spectroscopy techniques are well suited to archaeological and geological applications (Carr & Turner, 1996;McCutcheon, 1997;McCutcheon & Kuehner, 1997;Emerson & Hughes, 2000;Long, Silveira, & Julig, 2001;Wisseman et al, 2002;DeSouza et al, 2003;Lyons, Glascock, & Mehringer, 2003;Hubbard, Waugh, & Ortiz, 2005;Hubbard, 2006;Bowitz & Ehling, 2008;Hawkins et al, 2008;Ostrooumov, 2009;Parish, 2009;Wisseman et al, 2010).…”
Section: Vnir Spectroscopymentioning
confidence: 90%
“…The characterization and analysis of rock materials through reflection spectrometry allows heritage to be studied non-destructively [39]. The use of neural computing in remote sensing is useful as it delimits the physical frame from which to gather data from a material, in this case Lioz microcrystalline limestone.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, reflection spectra are not commonly used and literature on their application is scarce. Recently, however, reflection spectra have been shown to be a useful method for identifying minerals (Clark, 1999;Ostrooumov, 2009). Since no sample preparation involving destructive processes is necessary it is a good method for identifying gemstones (Hainschwang and Notari, 2008).…”
Section: Mineralsmentioning
confidence: 99%
“…Recently it has been shown that FTIR specular reflectance spectra can be used to distinguish between minerals and for imaging material properties of bone specimens (Acerbo et al, 2012;Nicolson et al, 2012, Ostrooumov, 2009). In the identification of gemstones the technique is gaining ground, and has been in use for quite some time for remote sensing of minerals (e.g., Hainschwang and Notari, 2008;Clark 1999).…”
Section: Introductionmentioning
confidence: 99%